ISOLATED HYPERTHERMIC CHEMOPERFUSION OF THE LIVER IN ITS METASTATIC LESIONS - N. A. Maistrenko; A. I. Babich; P. N. Romashchenko; Yu. A. Pobedinceva; V. M. Unguryan; V. A. Kudlachev; T. Yu. Kushtan; A. I. Strogonov (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The aim of the study is to evaluate the clinical efficacy of isolated hyperthermic liver chemoperfusion with melphalan and tumor necrosis factor alpha when it is isolated bilobate metastatic lesion and the ineffectiveness of systemic chemotherapy in patients with colorectal cancer. MATERIAL AND METHODS. The patient K, 67 y. o., with colorectal adenocarcinoma T3N0M1 (hep, 3 type). liver metastases were detected synchronously with the detection of the primary tumor. Resection of the primary tumor was performed at first, then there was systemic chemotherapy (6 FOLFOX and 3 FOLFIRI). The was tumor progression in liver after second-line chemotherapy. Isolated hyperthermic liver chemoperfusion was perfomed after complete vascular exclusion of the liver with parallel circulation to return blood to the system of the superior vena cava from the inferior vena cava and portal vein. hepatic perfusion in heart-lung machine with the chemotherapy drugs (melphalan and tumor necrosis factor alpha) carried out through the gastro-duodenal artery and back flow to the circulation circuit from the retro-hepatic vena cava. RESULTS. Using of the isolated hyperthermic liver chemoperfusion allowed reaching full necrosis of liver metastases that confirmed by histopathology results and CT data of the abdominal cavity in a month after the procedure. CONCLUSION. Isolated hyperthermic liver chemoperfusion with melphalan and tumor necrosis factor alpha is the effective method of regional chemotherapy, which is advisable in patients with unresectable isolated metastatic lesion of the liver and resistible to systemic chemotherapy.